Mapping Research trend in Covid 19 and energy - Marina Artiyasa; Marina; Muhammad Natsir; Panji Narputro; Dudih Gustian (Nusa Putra University, 2024)
This research delves into the bibliometric analysis of the interconnection between COVID-19 and energy, exploring the scholarly landscape and research trends in these critical areas. By employing bibliometric methods using biblioshiny to analyze publications, citation networks, and collaboration patterns, this study aims to uncover the impact and visibility of research from 2020-2023 from scopus index on keyword COVID-19 and energy. , average citation in document is 16,54.In H index , We can see that affiliation Energies. Have highest H index 14, the highest no of documents belongs to Klemes JJ with 12 documents, We can see that affiliation from China university of Petroleum (East China) have the highest production article in year 2023 reach nearly 20. in this data china have the highest corresponding authors countries , The treemap indicates the most frequently used keywords in articles,in this dataset about covid19 and energy we find Covid 19 and Energy utilization as the most common word. in emerging or declining themes we find covid 19, energy utilization and energy efficiency , and in motor themes we find human, human and corona virus disease 2019 , for basic themes and niche themes is empty